2022
DOI: 10.1111/joor.13360
|View full text |Cite
|
Sign up to set email alerts
|

Excessive mechanical stress induced temporomandibular joint osteoarthritis via osteoclasts‐mediated osteogenic differentiation of BMSCs

Abstract: Background: Bone homeostasis is a dynamic process maintained by osteoblasts and osteoclasts, which may be regulated by excessive mechanical stress (EMS).Objectives: Our study aimed to explore the relationship between osteogenic differentiation of BMSCs and EMS-activated osteoclast differentiation of RAW 264.7 cells in order to optimise orthodontic treatment. Methods:We established the model of EMS in vivo and in vitro. In vivo, HE, Safranin-O staining, micro-CT, and immunofluorescence double-labelling were uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Osteoblasts and osteoclasts are the main cells involved, and bone marrow mesenchymal stem cells (MSCs), osteocytes and chondrocytes also regulate the growth of osteoblasts and osteoclasts. Many studies have shown that when various cells involved in the regulation of bone metabolism (such as osteoblasts, osteoclasts, chondrocytes and MSCs) are exposed to external mechanical stimuli, the cells can convert external mechanical stimuli into intracellular bioelectrical stimuli through integrins on their surfaces 8 , 15 , 16 and activate related intracellular signalling pathways, thereby regulating the formation and degradation of bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts and osteoclasts are the main cells involved, and bone marrow mesenchymal stem cells (MSCs), osteocytes and chondrocytes also regulate the growth of osteoblasts and osteoclasts. Many studies have shown that when various cells involved in the regulation of bone metabolism (such as osteoblasts, osteoclasts, chondrocytes and MSCs) are exposed to external mechanical stimuli, the cells can convert external mechanical stimuli into intracellular bioelectrical stimuli through integrins on their surfaces 8 , 15 , 16 and activate related intracellular signalling pathways, thereby regulating the formation and degradation of bone tissue.…”
Section: Introductionmentioning
confidence: 99%